User-Centric Measures of the Perceived Light Qualities of Lighting Products - Carolina Hiller; Magdalena Boork; Johanna Enger; Karin Wendin (Ital Publication, 2023)
Nowadays, lighting planning is predominantly determined by the need to meet physically measurable requirements that are often based on current lighting standards. However, meeting the minimum technical requirements of the standards is no guarantee for a visually appealing light environment. Instead, requirements based on perceived light qualities also need to be included to achieve better user comfort. Taking perception-based qualities into consideration when creating a light environment is, for many, not an easy task. In addition, a common terminology for perceived light qualities is currently lacking, both in industry and in research. The aim of this paper is, therefore, to explore how perceived light qualities of white light sources can be described when employing user-centric measures. The focus was on the qualities of light colour and diffuse and distinct light since these qualities have a great impact on the visual impression of light. The perception was assessed by applying analytical sensory analysis to lighting products, a method found to be promising in previous work. The methodology is based on analytical measurement by the human senses, which is particularly valuable when developing a general terminology. Since sensory analysis is still quite new to the topic of lighting, the applicability of using the methodology to assess lighting in a real context was also investigated. The results of the studies showed that the perception of light qualities can be described using further concepts in addition to those currently used. For light colour, the concepts of reddish, bluish, yellowish, and greenish light colours proved suitable for providing a richer description of the quality. The concepts of diffuse and distinct light satisfactorily captured variations in light contrast produced by shadows, reflections, and sparkles. In addition, the studies revealed that analytical sensory analysis was applicable for assessing the perception of lighting in a real-world context. The latter means that knowledge gained in the laboratory can be translated into real environments. The user-centric measures investigated in this paper have contributed to the terminology related to perceived light qualities. These can complement the physical measures in lighting planning to promote light environments that are not only energy efficient and meet technical requirements, but also cater for increased user comfort. Doi: 10.28991/ESJ-2023-07-02-022 Full Text: PDF